Students’ Attitude and Gender as Determinants of Colleges of Education Students’ Academic Achievement in Chemistry (Lafia Journal of Scientific and Industrial Research, 2024)
The study examined students’ attitude and gender as determinants of Colleges of Education students’ academic achievement in chemistry. Three research questions were answered and three hypotheses were also tested. A correlation survey research design was adopted for the study.  The population for the study made up of all NCE III chemistry students (1,581) in the North East, Nigeria. A sample size of four hundred and twenty (420) NCE III chemistry students was obtained through multi-stage sampling procedure. An adapted structured questionnaire of Students Attitude Scale, SAS that made up of 2 clusters was used for data collection. A chemistry achievement tests (CAT) was also conducted. The instrument reliability test was done using Cronbach Alpha and index is 0.884 found to be valid and reliable. Data analysis was done using Pearson’s product moment correlation and ANOVA to test the hypotheses at 5% level of significance. The findings showed a significant relationship between students’ positive attitude to chemistry and their academic achievement in chemistry. It was on this note that, a recommendation is made among others factors that NCE chemistry lecturers should make their teaching approaches more stimulating and interesting as to produce a positive attitude from students to chemistry courses and towards their chemistry lecturers. Thereby, create a better learning ability in them for a high academic achievement in chemistry at Colleges of Education
Keywords: Attitude; Gender; Academic Achievement; Chemistry; Education